Prototype Alat Pemilah Sampah Organik, Logam, dan Non Logam Menggunakan Mikrokontroler Esp32 - Saputra, Riki; Ch, Syafaruddin; Paniran, Paniran (BEES: Bulletin of Electrical and Electronics Engineering, 2024)
The issue of waste management has become increasingly important alongside the growth of population and public consumption. Improper disposal of waste types leads to environmental and health problems. To address this, it is necessary to develop technology that can aid in the efficient sorting of waste. This study aims to: first, design and build a waste sorter for organic, metal, and non-metal waste using the ESP32 microcontroller; and second, understand the operating system of the organic, metal, and non-metal waste sorting device. This research utilizes a design and implementation method for the waste sorter based on the ESP32 microcontroller. The device is equipped with capacitive and inductive proximity sensors to detect waste types, as well as a servo motor to direct waste into the appropriate collection bins. The results of this study indicate that: first, the designed waste sorter can sort waste into three categories: organic, metal, and non-metal. Second, the capacitive and inductive proximity sensors can effectively detect waste types at a range of 2-6 cm. Third, the servo motor can drive the sorting mechanism to direct waste to the appropriate collection bins. Fourth, this waste sorter can help improve efficiency and accuracy in waste management.